Therapeutic Targeting of Long Non-Coding RNAs in Cancer. Issue 3 (March 2018) - Arun, Gayatri; Diermeier, Sarah D.; Spector, David L.
Abstract : Long non-coding RNAs (lncRNAs) represent a significant population of the human transcriptome. Many lncRNAs exhibit cell- and/or tissue/tumor-specific expression, making them excellent candidates for therapeutic applications. In this review we discuss examples of lncRNAs that demonstrate the diversity of their function in various cancer types. We also discuss recent advances in nucleic acid drug development with a focus on oligonucleotide-based therapies as a novel approach to inhibit tumor progression. The increased success rates of nucleic acid therapeutics provide an outstanding opportunity to explore lncRNAs as viable therapeutic targets to combat various aspects of cancer progression. Highlights: Approximately 27% of annotated human genes encode lncRNAs. Recent tumor genome sequencing efforts have identified several lncRNA loci that are deleted, amplified, and/or mutated in various cancers. Many lncRNAs are up- or downregulated in cancers compared to respective normal tissues. Several lncRNAs have been shown to play a crucial role in various aspects of cancer progression. Tissue-specific expression of lncRNAs positions them as interesting potential therapeutic targets for a variety of pathologies. Nucleic acid-based therapeutics are emerging as a promising approach to target pathogenic lncRNAs. RNA-targeting therapies have been clinically approved for several diseases. Nucleic acid-based therapeutics have shown success in several preclinical studies targeting lncRNAs in cancers.